Postpartum Vesicovaginal Fistulas: Risk Factors, Prevention and Treatment Strategies - Amjad, Maliha; Amna Rehman,; Umm-e-Habiba,; Adeeba Fatima,; Naveed,; Aisha Butt, (Indus Journal of Bioscience Research, 2025)
Background: Postpartum vesicovaginal fistulas (VVFs) are a significant complication of childbirth, particularly in low-resource settings, leading to long-term physical and psychosocial challenges for affected women. Objective: This study aims to identify the key risk factors, assess the effectiveness of prevention strategies, and evaluate surgical treatment outcomes for postpartum VVFs. Methods: This retrospective cohort study was conducted at Avicenna Hospital, Lahore, July to December 2024. A total of 123 women diagnosed with postpartum VVFs were included in the study. Data were collected through retrospective chart reviews and structured patient interviews. Key variables extracted from medical records included demographic information such as age, education level, and socioeconomic status. Results: The majority of the participants (72%) were multiparous, and 56% of cases were associated with obstructed labor. Women with inadequate antenatal care (28%) and those attended by non-skilled birth attendants (14%) had a significantly higher risk of developing VVFs. Surgical repair was successful in 85% of cases, with vaginal repair achieving an 80% success rate. Post-surgical complications, such as infections and urinary retention, were minimal, affecting 8% and 4% of the cases, respectively. A notable psychosocial impact was observed, with 65% of women reporting emotional distress and 59% experiencing social isolation due to the condition. Conclusions: Postpartum VVFs are strongly associated with obstructed labor, prolonged delivery, and inadequate antenatal care. Early intervention and skilled birth attendance are crucial for preventing VVFs.